A clinical study of liposuction followed by lymphovenous anastomosis for treatment of breast cancer-related lymphedema - Kun Chang; Song Xia; Chen Liang; Yuguang Sun; Jianfeng Xin; Wenbin Shen (Frontiers in Surgery, 2023)
ObjectiveIn this work, we studied the clinical effect of liposuction followed by lymphovenous anastomosis (LVAs) for the treatment of breast cancer-related lymphedema (BCRL).MethodsWe analyzed 158 patients with unilateral upper limb BCRL who underwent liposuction followed by LVAs 2–4 months later. Arm circumferences before and 7 days after the combined treatments were prospectively recorded. Circumferences of different upper extremities were measured before the procedure, 7 days after LVAs, and during the follow-ups. Volumes were calculated with the frustum method. During the follow-ups, the conditions of patients’ treated arms, i.e., the frequency of erysipelas episodes and dependence on compression garments, were recorded.ResultsThe mean circumference difference between two upper limbs decreased significantly from M (P25, P75) of 5.3 (4.1, 6.9) preoperatively to 0.5 (−0.8, 1.0) (P < 0.05) 7 days after treatments, while at follow-up 0.3 (−0.4, 1.0). The mean volume difference decreased significantly from M (P25, P75) of 838.3 (662.4, 1,129.0) preoperatively to 7.8 (−120.3, 151.4) (P < 0.05) 7 days after treatments, while at follow-up 43.7 (−59.4, 161.1). The incidence of erysipelas also significantly decreased (P < 0.05). 6.3% of patients were already independent of compression garments during the past six months or even more.ConclusionLiposuction followed by LVAs is an effective method for the treatment of BCRL.